Geological map of Jutulsessen (Dronning Maud Land) - Elvevold, Synnøve; Engvik, A K; Hansen, C; Jacobs, J; Meiklejohn, I; Myhre, P I; Rudolph, E (Norsk Polarinstitutt, 2021)
Publication Title: Temakart; 54 Place: Tromsø
Keywords: Dronning Maud Land; geologi; kart

Norway and the Antarctic - Stephenson, Robert B; [Barr, Susan] (The Erebus and Terror Press, 2017)
Pages: 14 s. Publication Title: Norway and the Antarctic : SouthPole-sium v.3 Place: New Hampshire
Keywords: Antarktis; Nordmenn; norske ekspedisjoner; polarfarere

East Antarctica and supercontinent configuration: the Dronning Maud Land perspective - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Jokat, Wilfried (Japan Geoscience Union, 2015)
The geology of East Antarctica and its correlation in major supercontinents is highly speculative, since only a very small part of it is exposed. Therefore a better connection between geology and geophysics is needed in order to correlate exposed regions with ice-covered, geophysically-defined, blocks. In Dronning Maud Land (DML), two distinct late Mesoproterozoic/early Neoproterozoic tectono-metamorphic provinces appear, separated by the major, NE-trending Forster Magnetic Anomaly and South Orvin Shear Zone. To the west of this lineament, the Maud Belt has clear affinities with Grenville-age continent-continent mobile belts. East of the Forster Magnetic Anomaly, juvenile rocks with early Neoproterozoic age (Rayner-age) and an accretionary character crop out. The international GEA-II expedition (2012) targeted a white spot on the geological map immediately to the E of the Forster Magnetic Anomaly. This area allows the characterization and ground-truthing of a large and mostly ice-covered region, the SE DML Province that had previously been interpreted as an older cratonic block. However, new SHRIMP/SIMS zircon analyses and their geochemistry indicates that the exposed basement consists of a ca. 1000-900 Ma juvenile terrane that is very similar to rocks in Sor Rondane. It lacks significant metamorphic overprint at the end of crust formation, but it shows medium to high-grade overprinting between ca. 630-520 Ma, associated with significant felsic melt production, including A-type granitoid magmatism. Therefore, the aeromagnetically distinct SE DML province does neither represent the foreland of a Late Neoproterozoic/EarlyPaleozoic mobile belt, nor a craton, as has previously been speculated. It more likely represents the more juvenile, westward continuation of Rayner-age crust (1000-900 Ma). To the west it abuts along the NE-trending Forster Magnetic Anomaly. The latter is interpreted as a suture, which separates typical Grenville-age crust of the Maud Belt (ca. 1200-1030 Ma) to the W from Rayner-age crust to the E. Therefore the larger eastern part of DML has clearly Indian affinities. Its juvenile character with a lack of metamorphic overprint at the end of crust formation points to an accretionary history along this part of the Indian segment of Rodinia, immediately following final Rodinia assembly.
Publication Title: Japan Geoscience Union meeting Place: Chiba-city, Japan
Keywords: Dronning Maud Land; geofysikk; geologi

Roald Amundsens sydpolsferd (1910-1912) = Roald Amundsen's South Pole expedition (1910-1912) - Amundsen, Roald; Diesen, Jan Anders; Lund, Harald Østgaard (Norsk filminstitutt, 2010)
Publication Title: Roald Amundsen's South Pole expedition (1910-1912) Place: Oslo
Keywords: Antarktis; Fram (skip); Norge; Sydpolen; Sydpolsekspedisjonen; dokumentarfilmer; ekspedisjonsfilmer; oppdagelsesreiser; polarområdene

Radar Scattering Zones across Dronning Maud Land, East Antarctica - Müller, Karsten; Albert, Mary; Hamran, Svein Erik; Hagen, Jon Ove Methlie (International Glaciological Society, 2008)
Publication Title: International Symposium on Radioglaciology and its Applications Place: Madrid, Spain
Keywords: Dronning Maud Land; geovitenskap; glasiologi

Digestibility of krill in crabeater seals and minke whales - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (1993)
Pages: 73 Publication Title: 10th Biennial Conference on the Biology of Marine Mammals Place: Galveston, Texas, USA
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Satellite tracking of crabeater seals off Queen Maud Land in Antarctica - Nordøy, Erling S; Folkow, Lars P; Blix, Arnoldus Schytte (1993)
Pages: 81 Publication Title: 10th Biennial Conference on the Biology of Marine Mammals Place: Galveston, Texas, USA
Keywords: Dronning Maud Land; satellitt; seler; telemetri; zoologi

Development of chicks during extreme cold conditions: the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (University of Ottawa Press, 1988)
Pages: 1447-1456 Publication Title: Acta XIX Congressus Internationalis Ornithologici Volume: 2 Place: Ottawa, Canada
Keywords: Dronning Maud Land; fugler; konferanse; kongress; ornitologi; zoologi

Oversikt over naturområder og forekomster i Norge og polarområdene som er fredet eller vernet pr. 1. januar 1985 (Miljødepartementet, 1985)
Pages: 96 s. Place: Oslo
Keywords: Bouvetøya; kultur; miljøvern; naturvern; polarområdene

Iceberg discharge and the mass balance of Antarctica - Orheim, Olav (National Academy Press, 1985)
Pages: 210-215 Publication Title: Glaciers, Ice Sheet, and Sea Level: Effects of a CO2 - Induced Climatic Change Place: Seattle, Washington
Keywords: Antarktis; glasiologi; innlandsis; isberg; isbreer

Adaptation to low temperature in Antarctic terrestrial arthropods - Sømme, Lauritz (Comite National Francais Des Recherches Antarctiques, 1982)
Pages: 219-225 Publication Title: Colloque sur les ecosystèmes subantarctiques Volume: 51 Place: Station Biologique de Paimpont, Université de Rennes, France
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Sea bed feauters in the Blåenga area, Weddell Sea, Antarctica - Lien, Reidar (Université Laval, 1981)
Pages: 706-716 Publication Title: POAC 81 : The Sixth International Conference on Port and Ocean Engineering under Arctic Conditions Volume: 2 Place: Quebec, Canada
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; geologi; havbunnen; kongress; oseanografi; symposium

Botaniske undersøkelser på Bouvetøya : om materialet som ligger til grunn og dets videre bearbeiding - Engelskjøn, Torstein (1979)
Pages: 10 s. + to stensilerte vedlegg Place: [Oslo]
Keywords: Bouvetøya; NARE 1978/79; botanikk; ekspedisjoner

On the drift ice conditions in the Atlantic sector of the Antarctic - Vinje, Torgny E (The Norwegian Institute of Technology, 1979)
Pages: 75-82 Publication Title: POAC 79 : The Fifth International Conference on Port and Ocean Engineering Under Arctic Conditions Volume: 3 Place: Trondheim, Norway
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; konferanse; oseanografi; sjøis

Forslag til maringeofysiske undersøkelser ved Bouvetøya - Kristoffersen, Yngve ([Norsk Polarinstitutt], 1978)
Pages: [14] s. Publication Title: Antarktisekspedisjonen 78/79 Place: [Oslo]
Keywords: Bouvetøya; NARE 1978/79; marin geofysikk

Polarområdenes økosystemer - Larsen, Thor (1978)
Pages: 8 s. Place: [Oslo]
Keywords: Antarktis; polarområdene; økologi

Global glacier mass balance variations during the past 300 years - Orheim, Olav (Arctic Institute of North America, 1977)
Pages: 667-681 Publication Title: Polar Oceans Place: McGill University, Montreal, Canada
Keywords: Antarktis; glasiologi; is; isbreer; klimaendringer; konferanse; polarområdene; stratigrafi; symposium

Past and present mass balance variations and climate at Deception Island, South Shetland Islands, Antarctica - Orheim, Olav (International Association of Hydrological Sciences, 1975)
Pages: 161-180 Publication Title: Snow and Ice. Symposium. Neiges et Glaces: IAHS-AISH Publication Snow and Ice Symposium. Proceedings of the Moscow Symposium Volume: 104 Place: Moscow, Russia
Keywords: Antarktis; forskning; glasiologi; klimatologi

Svalbard - Jan Mayen - The Antarctic Possessions (Utenriksdepartementet, 1973)
Publication Title: Norway Information Volume: UDA 297/73 Place: Oslo
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Theories of bottom water formation, recent investigations in the Weddell Sea and the effects of super cooling by the ice cap - Mosby, Håkon (Japan Society for the Promotion of Science, 1971)
Pages: 126-127 Publication Title: The Ocean world : proceedings of Joint Oceanographic Assembly, IAPSO, IABO, CMG, SCOR Place: Tokyo, Japan
Keywords: Sørishavet; Weddellhavet; bunnvannet; kongress; oseanografi; sjøvann

Geology of western Queen Maud Land - Roots, Ernest Frederick (American Geographical Society, 1969)
Pages: Folio 12. Geologic map of Antarctica. Sheet 6 Publication Title: Antarctic Map Folio Series Place: [New York]
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi

Hvalfangstforhandlingene 1958-1962. Et eksempel på "distributive bargaining" - Overrein, Per Narve (1968)
Pages: [57 s.] Publication Title: [En nordisk statsvetarkonferens] Place: Gøteborg
Keywords: Sørishavet; historie; hvalfangst; hvalfangstkvoter; internasjonal; pelagisk; politikk

Bottom water formation - Mosby, Håkon (SCAR/SCOR/IAPO/IUBS, 1966)
Pages: 47-57 Publication Title: Symposium on Antarctic Oceanography Place: Santiago, Chile
Keywords: Sørishavet; Weddellhavet; bunnvann; bunnvannsformasjoner; havstrømmer; oseanografi; sjøvann

South Atlantic bottom water - Mosby, Håkon (Scientific Committee on Antarctic Research, 1966)
Pages: 11-20 Publication Title: Symposium on Antarctic Ice and Water Masses Place: Tokyo, Japan
Keywords: Sørishavet; Weddellhavet; bunnvann; bunnvannsformasjoner; havstrømmer; oseanografi; sjøvann

En del sovjetiske forskningsinstitusjoner, med særlig vekt på de som arbeider med oppgaver i arktiske og antarktiske strøk - Heintz, Natascha ([Norsk Polarinstitutt], 1965)
Pages: 18 s. Place: Oslo
Keywords: Antarktis; forskning; polarområdene; vitenskap

Studies on the southern stocks of Blue and Fin whales - Jonsgård, Åge; Ruud, Johan T (Hermann, 1964)
Pages: 333-344 Publication Title: Biologie Antarctique : premier symposium organise par le S.C.A.R. Place: Paris, France
Keywords: Sørishavet; biologi; dyreliv; hvaler; hvalfangst; marinbiologi

Bouvetøya : et norsk biland - Mathiesen, Per (1958)
Place: [s.l.]
Keywords: Bouvetøya; geografi

Bouvetøya - Bureau, Weather (Weather Bureau, 1954)
Pages: [14] s. Place: Pretoria
Keywords: Bouvetøya; ekspedisjoner; historie; meteorologi

On the birds of Peter I Island - Holgersen, Holger (Almqvist and Wiksell, 1951)
Pages: 614-616 Publication Title: Proceedings of the Xth international ornithological congress Place: Uppsala
Keywords: Peter I. Øy; fugler; konferanser; ornitologi

Antarktiske fugler - Holgersen, Holger (Stavanger Museum. Naturhistorisk avdeling, 1949)
Pages: 22 s., ill. Place: Stavanger
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; zoologi

Who discovered Antarctica? - Aagaard, Bjarne (1939)
Pages: 675-707 Publication Title: Sixth Pacific Science Congress Place: San Francisco and Berkeley, California
Keywords: Antarktis; historie; historikk; oppdagelsesreiser

Atlas over Antarktis og Sydishavet : utgitt av Hvalfangernes Assuranceforening i anledning av foreningens 25-års jubileum - Hansen, Hans Edvard (red.) (Hvalfangernes Assuranceforening, 1936)
Pages: 17 bl. kart Place: Oslo
Keywords: Antarktis; Nordmenn; Norge; Sørishavet; hvalfangst; kartlegging; norske ekspedisjoner; oppdagelsesreiser

Omkring Löitnant Shirase's Sydpolarexpedition 1910-12 - Hamre, Ivar ([forfatteren], 1932)
Pages: 34 s. Place: Oslo
Keywords: Antarktis; Choku Shirase; Den japanske antarktisekspedisjonen 1910–12; Sydpolen; ekspedisjoner; oppdagelsesreiser

25 års hvalfangst i Sydishavet (Thrane-Nielsen A/S, 1930)
Pages: 1 ark folio Place: Oslo
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri

Utenriksk fangst : hvalfangst - Bogen, Hans
Pages: 22 s.
Keywords: Bouvetøya; Peter I. Øy; Sørishavet; historie; hvalfangst; oppdagelsesreiser; pelagisk; polarområdene

Politiske forhold i Antarktis - Giæver, John Schjelderup ([s.n.])
Pages: 24 s. Place: [S.l.]
Keywords: Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; historie; internasjonal politikk; opdagelsesreiser; rett

Dronning Maud Land : proposed Norwegian names - [Marstrander, C.]
Pages: 11 s.
Keywords: Dronning Maud Land; geografi

Journal over flyvninger utført under Lars Christensens ekspedisjon 1936/37 - Romnæs, Nils
Pages: 3 s. Place: [Oslo]
Keywords: Antarktis; Thorshavn ekspedisjon; flyfoto; flyvninger; kartlegging; luftfoto